EXPLORATION OF THE VALUE OF LOCAL WISDOM OF THE CIRENDEU INDIGENOUS COMMUNITY AS A SOURCE OF ISLAMIC CHARACTER EDUCATION - Nadri Taja; Rika Sartika (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
The life of the Cirendeu indigenous people has become one of the village icons with a unique culture that is diverse in their customs and traditions. The culture of this community is classified as still holding a fairly strong tradition from its ancestors, marked by socio-cultural conditions which are prerequisite for the values of local wisdom. So that the complex substance of the values of local wisdom in the Cirendeu community can be revealed as a source of Islamic character education in this study. This research uses ethnographic methods to explore the values of local wisdom in the Cirendeu indigenous people. The results show that in the religious aspect, there are four main points, namely the prohibition of taking the rights of others, the prohibition on imposing other people's beliefs, mutual cooperation and tolerance. In the socio-cultural aspect, it shows that the indigenous people of Cirendeu are principled and adhere to the old traditions and follow the flow of changing times (protecting the time of the era). Meanwhile, the source of Islamic character education from the indigenous Cirendeu community refers to the meaning of symbolic, empirical, aesthetic, ethical, synoetic, and synoptic life.